A trait‐based framework for predicting foodborne pathogen risk from wild birds. Issue 2 (10th February 2022) - Smith, Olivia M.; Olimpi, Elissa M.; Navarro‐Gonzalez, Nora; Cornell, Kevin A.; Frishkoff, Luke O.; Northfield, Tobin D.; Bowles, Timothy M.; Edworthy, Max; Eilers, Johnna; Fu, Zhen; Garcia, Karina; Gonthier, David J.; et al.
Abstract: Recent foodborne illness outbreaks have heightened pressures on growers to deter wildlife from farms, jeopardizing conservation efforts. However, it remains unclear which species, particularly birds, pose the greatest risk to food safety. Using >11, 000 pathogen tests and 1565 bird surveys covering 139 bird species from across the western United States, we examined the importance of 11 traits in mediating wild bird risk to food safety. We tested whether traits associated with pathogen exposure (e.g., habitat associations, movement, and foraging strategy) and pace‐of‐life (clutch size and generation length) mediated foodborne pathogen prevalence and proclivities to enter farm fields and defecate on crops. Campylobacter spp. were the most prevalent enteric pathogen (8.0%), while Salmonella and Shiga‐toxin producing Escherichia coli (STEC) were rare (0.46% and 0.22% prevalence, respectively). We found that several traits related to pathogen exposure predicted pathogen prevalence. Specifically, Campylobacter and STEC‐associated virulence genes were more often detected in species associated with cattle feedlots and bird feeders, respectively. Campylobacter was also more prevalent in species that consumed plants and had longer generation lengths. We found that species associated with feedlots were more likely to enter fields and defecate on crops. Our results indicated that canopy‐foraging insectivores were less likely to deposit foodborne pathogens on crops, suggesting growers may be able to promote pest‐eating birds and birds of conservation concern (e.g., via nest boxes) without necessarily compromising food safety. As such, promoting insectivorous birds may represent a win‐win‐win for bird conservation, crop production, and food safety. Collectively, our results suggest that separating crop production from livestock farming may be the best way to lower food safety risks from birds. More broadly, our trait‐based framework suggests a path forward for co‐managing wildlife conservation and food safety risks in farmlands by providing a strategy for holistically evaluating the food safety risks of wild animals, including under‐studied species.